2016
DOI: 10.1080/0886022x.2016.1184924
|View full text |Cite
|
Sign up to set email alerts
|

Long–term mortality after parathyroidectomy among chronic kidney disease patients with secondary hyperparathyroidism: a systematic review and meta-analysis

Abstract: Parathyroidectomy (PTx) and medical treatments are both recommended for reducing serum intact parathyroid hormone (iPTH) and curing secondary hyperparathyroidism (sHPT) in patients with chronic kidney disease (CKD), but their therapeutic effects on long-term mortality are not well-known. Thus, we aim to assess such therapeutic effect of PTx. Electronic literatures published on Pubmed, Embase, and Cochrane Central Register of Controlled Trials in any language until 27 November 2015 were systematically searched.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 53 publications
5
35
0
1
Order By: Relevance
“…Preoperative lab values indicate that 2HPT patients have markers indicating poorer renal function. It is also well known that 2HPT is associated with increased cardiovascular mortality . Ishani et al specifically studied dialysis patients with 2HPT and noted a pronounced association between PTX and increased hospitalizations, intensive care unit admission, duration of hospitalization, and emergency department visits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative lab values indicate that 2HPT patients have markers indicating poorer renal function. It is also well known that 2HPT is associated with increased cardiovascular mortality . Ishani et al specifically studied dialysis patients with 2HPT and noted a pronounced association between PTX and increased hospitalizations, intensive care unit admission, duration of hospitalization, and emergency department visits.…”
Section: Discussionmentioning
confidence: 99%
“…It is also well known that 2HPT is associated with increased cardiovascular mortality. 33 Ishani et al 34 specifically studied dialysis patients with 2HPT and noted a pronounced association between PTX and increased hospitalizations, intensive care unit admission, duration of hospitalization, and emergency department visits. During the hospitalization and the 30 days immediately after discharge, the mortality rate was 2.0%.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis by Chen et al demonstrated that parathyroidectomy reduced all-cause mortality in haemodialysis patients by 28%. 25,26 Although HBS is an undesirable consequence of parathyroidectomy, in our study the HBS group were more likely to achieve PTH normalisation (4.49 vs 11.75 pmol/L, P = 0.021). These patients may confer mortality benefit due to reduced vascular calcification and cardiovascular events in the long term.…”
Section: Discussionmentioning
confidence: 45%
“…Despite of fact that microvascular dysfunction was no reverted after PTX, recent systematic review and meta-analysis demonstrated that PTX was associated with decreased risks of all-cause and cardiovascular mortalities compared to medical treatments in CKD patients with SHPT. 9 In conclusion, paper from Silva et al is really welcome. It is important to highlight that our understanding of the cardiovascular manifestations of SHPT remains still incomplete.…”
Section: Risk Factors Associated With Subendocardial Ischemia In Hemomentioning
confidence: 96%